2017
DOI: 10.1007/s12011-017-1128-6
|View full text |Cite
|
Sign up to set email alerts
|

Chromium Supplementation Reduces Resting Heart Rate in Patients with Metabolic Syndrome and Impaired Glucose Tolerance

Abstract: Chromium (Cr) is considered as an important mineral, involved in biochemical reactions in human metabolic pathways. Organically bound Cr supplementation has been suggested to improve glycemia especially in patients with type 2 diabetes mellitus, but there are conflicting reports on efficacy. Effect of Cr is not clear in prediabetes status. Seventy patients with metabolic syndrome and impaired glucose tolerance (IGT), who are observed and treated in the Center of Preventive Cardiology of the University Hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 27 publications
0
27
0
1
Order By: Relevance
“…Different forms of chromium were used in the included trials. Of all included trials, 17 trials administered chromium picolinate, two trials administered the intervention as chromium‐enriched yeast and three trials used the nicotinate form of chromium as the interventional compound . Duration of chromium supplementation varied between 9 and 24 weeks with a median of 12 weeks.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Different forms of chromium were used in the included trials. Of all included trials, 17 trials administered chromium picolinate, two trials administered the intervention as chromium‐enriched yeast and three trials used the nicotinate form of chromium as the interventional compound . Duration of chromium supplementation varied between 9 and 24 weeks with a median of 12 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…Changes in BMI were reported in eight trials and 19 trials reported changes in body weight . The reported mean BMI of all included trials was over 25 kg/m 2 , therefore all included participants were considered as subjects with overweight/obesity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations